2014
DOI: 10.1123/rsj.2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Adults' Motivation for Physical Activity: Differentiating Motives for Exercise, Sport, and Recreation

Abstract: Physical inactivity continues to be a significant problem that adversely impacts adult health. An important construct to consider in researching adult physical activity adherence is motivation. Factors motivating participation in two types of physical activity, exercise and sport, have been compared; however, factors motivating participation in another type of physical activity, recreation, have often been left out of the comparison. The current study compared motivation to partake in physical activity among a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
1
25
0
3
Order By: Relevance
“…Although the reasons for participation to physical activity are highly complex, one of the most significant factors that stimulate and maintain physical activity participation is motivation . Motivation is a psychological concept that encourage an individual toward a desired goal and is regarded a psychological force that includes the intention and direction to engage in a certain behavior (Ball, Bice, & Parry, 2014). Motives has a key role in every aspect of life, in participation to physical activity as well (Çetin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the reasons for participation to physical activity are highly complex, one of the most significant factors that stimulate and maintain physical activity participation is motivation . Motivation is a psychological concept that encourage an individual toward a desired goal and is regarded a psychological force that includes the intention and direction to engage in a certain behavior (Ball, Bice, & Parry, 2014). Motives has a key role in every aspect of life, in participation to physical activity as well (Çetin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas in a study that examined motivational orientations, it was found that participants who used exercise and recreation activities as their primary form of physical activity are motivated by more extrinsic constructs (i.e., weight management) than those who engage in sports. Those that used sport as their primary form of physical activity reported more intrinsically motivated orientations, like competition and enjoyment (Ball, Bice, & Parry, 2014). These studies begin to portray a complex picture of how individual identity could be tied to the type of athletic endeavors.…”
Section: In Consideration Of the Research Questionmentioning
confidence: 99%
“…James Warren Ball and colleagues [6] stated that recreational sports are the main factor that can nurture the fitness and physical resilience of adults in the city of Chicago, but consistency in exercising should be owned by everyone in order for physical fitness to be retained, to further assist the consistency it is necessary the presence of a good and comfortable area for adults to do sports that its nature of recreation. Thus, it can be explained that the development of tourist areas as a recreational sports field worth doing for the interests and needs of many communities.…”
Section: Based On the Law Of The Republic Of Indonesia Number 3 Year mentioning
confidence: 99%